CuInSe2 THIN FILM FOR SOLAR CELL BY FLASH EVAPORATION - Soepardjo, A H (Makara Journal of Science, 2009)
Deposition of thin films for material solar cell CuInSe2 are relatively simple. In this research mainly focused on the use of flash evaporation method, and the material created can then be characterized by optical and electrical properties. The optical characterization is done by X-ray Diffraction (XRD), Energy Dispersive Spectroscopy (EDS), and transmission and reflection by UV-VIS spectrophotometry. Electrical characterization is done by utilizing the Hall effect equipment. From these characterization, the atomic structure, absorption coefficient, energy gap, material type, composition of each elements and the mobility of CuInSe2 can be measured and determined. During process evaporation were carried out at substrate temperatures the range between 20ºC–415ºC.